ALAM DAN MANUSIA “SEBUAH KESATUAN YANG DIPISAHKAN WACANA” - Banu Prasetyo (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2020)
Human civilization progress is linked to the development of science. The era of revolutionary industry 4.0 has a passion to encourage people to better understand the higher realms of humanity from the ecosystem itself, but in reality condition, human relationships and nature as separate from each other, when they live in one unity. On the other hand, a religion that turns into a worldview also does not give the spirit of the unity of man and nature. This issue can be applied by the Javanese culture by offering a philosophy of the memayu hayuning bawana philosophy that seeks to reunite the unity between man and nature.